The Concept of Marriages of Convenience in EU Free Movement Law : EU and UK Perspectives - Ancite-Jepifánova, Aleksandra, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
Over the past two decades, EU Member States have regularly complained about the perceived abuse of EU law via marriages of convenience, allegedly contracted between mobile EU citizens and third-country nationals. During the pre-Brexit years, the UK had been voicing particularly strong concerns about the issue, which ultimately resulted in regulatory changes both at the EU and national level. In this book, Aleksandra Ancite-Jepifánova pursues two interrelated aims. First, she evaluates the compatibility of EU-level measures addressing marriages of convenience with EU free movement law by focusing on the Citizenship Directive. Second, she examines the regulation of the issue in UK law in so far as it concerns the residence rights of EU citizens and their family members, both pre-and post-Brexit. See Less